The role of the personnel practitioner in the identification and handling of communication problems in organisations - L.D. Coetsee (Communicare)
The scope of the personnel practitioners' role has, over the past decade, grown from the traditional activities of inter alia, manpower recruitment, selection and training to include organisational diagnoses and maintaining and improving organisational effectiveness and the quality of work life of employees. The complex organisation in which the practitioner has to fulfil these roles, consists of differentiated but interdependent sub-systems linked by resource and information flows. Information can be described as the bloodstream of an organisation and communication channels as the arterial system. To fulfil his role the personnel practitioner has to have means and instruments to gather information on all relevant aspects of organisation and its sub-systems. In this paper the important role of information in organisational functioning and behaviour is described, as well as ways to gather information systematically and how the personnel practioner can use ] this information to maintain and improve organisational effectiveness and the quality of work life of employees